Measuring the Potential Integration of Indonesian Sharia Capital Market with the OIC Member Countries - Anita; Asep Dadan Suganda; Ratu Humaemah (Journal of Islamic Economics and Finance Studies, 2023)
The Indonesian Composite Index (ICI) experienced a critical session, the data showed the ICI fell by 6.58% which was the biggest decline in the last 9 years. The prevailing notion was that this pressure stemmed from the prevalence of the Covid-19 concern and is anticipated to be alleviated once Covid-19 disseminates further. The purpose of this study is to determine the causality and long-term cointegration relationship between sharia stock in Indonesia and the Organization of Islamic Cooperation (OIC) member countries, as well as to determine the contribution of shares of OIC member countries, such as Egypt, Oman, Saudi Arabia, Kuwait, Turkey, Bahrain, and Malaysia in the collapse of the Islamic capital market in Indonesia. The method used in this research is quantitative by using secondary data in the form of daily prices of the Sharia index sourced from the website www.investing.com. The population of the countries related to this research is 56 members of the OIC that are active until 2021. For data analysis, several tests were conducted, such as; Testing Time Series Data, Vector Autoregressive (VAR), Granger Causality Test, Johansen Model Cointegration Test, and Contagion Effect Test. The study found that; has not been able to prove the existence of cointegration between the Indonesian Islamic stock exchange and the stock exchanges of OIC member countries other than the Malaysian stock exchange. However, this study proves the interdependence between the Malaysian and Indonesian Islamic stock exchanges, but in the long term, the contribution of the Indonesian stock exchange is greater than the Malaysian Islamic stock index. In addition, another finding was that during the Covid-19 shock, the Malaysian stock position index showed more independence, whereas the decline that occurred at the beginning of the pandemic was caused without the JII or ISSI intervention index.